About the Need of Studying Subjects with Ethnocultural Component in Yugra - Natalia V. Tkachuk (Publishing house "Sreda", 2021)
The author has studied the sociolinguistic experience of conducting regional studies among the titular ethnic groups of Ugra. The purpose of the article is to to find out the need to study subjects with ethno-cultural content in Ugra schools by using the questionnaire survey among the indigenous small-numbered peoples of the Kondinsky district. The subject of the study is the indigenous ethnic groups of Ugra - Khanty, Mansi, Nenets. Research methods. The theoretical and methodological foundations of ethno-cultural education are studied. The work used sociological data obtained by questionnaire collection of material. 684 questionnaires were systematized on the basis of the software for processing and analyzing sociological information «Vortex». The article emphasizes the importance of preserving, supporting and using the native languages of the titular peoples of Ugra. As a result of the study, a picture describing the vitality of the indigenous languages of the study area was obtained, and the need for educational subjects with an ethno-cultural component was established. The problem of preserving native languages is acute. In the teaching the subjects with the ethno-cultural component, the motivation and ethnic self-consciousness of the participants themselves (representatives of indigenous small-numbered peoples) are important, who, by their own will, can positively influence the socio-cultural processes of ethnic communities, the linguistic stability and prospects of national languages.